The intellectual landscape in the works of J. M. Coetzee - Mehigan, Tim 1960-; Moser, Christian 1963- (Boydell & Brewer, 2018)
New essays examining the intellectual allegiances of Coetzee, arguably the most decorated and critically acclaimed writer of fiction in English today and a deeply intellectual and philosophical writer
J. M. Coetzee on truth, skepticism, and secular confession in "The Age We Live in" / Tim Mehigan -- Social order and transcendence : J. M. Coetzee's poetics of play / Christian Moser -- Autobiography and romantic irony : J. M. Coetzee and Roland Barthes / Patrick Hayes -- The semantics of barbarism in J. M. Coetzee's novel Waiting for the Barbarians / Markus Winkler -- In the heart of the empire : Coetzee and America / Martin Woessner -- Faith, irony, salt, and possible impossibilities : J. M. Coetzee's the childhood -- Of Jesus in conversation with Zbigniew Herbert's "From Mythology" / Maria Boletsi -- Coetzee's ethics of language(s) / Robert Stockhammer -- Force fields / Carrol Clarkson -- The reading of Don Quixote : literature's migration into a new world / Alexander Honold -- The lives of animals : from rational language to speaking (of) lions / Elisa Aaltola -- Coetzee as academic novelist / Simon During -- Character and counterfocalization : Coetzee and the Kafka lineage / Derek Attridge -- J. M. Coetzee's South African intellectual landscapes / David Attwell -- Philosophical fiction? On J. M. Coetzee's Elizabeth Costello / Robert B. Pippin -- Cosmopolitanism, the range of sympathy, and Coetzee / Anton Leist. - Title from publisher's bibliographic system (viewed on 31 Jul 2019)
Keywords: Coetzee, J. M. / 1940- / Criticism and interpretation; Coetzee, J. M. -- 1940-; Aufsatzsammlung